Change in glottic view during intubation using a KoMAC videolaryngoscope: A retrospective analysis. Issue 9 (3rd March 2023) - Shin, Hyun-Jung; Kim, Hyeong Geun; Park, In-Sun; Nam, Sun Woo; Park, Jin-Hyoung; Hwang, Jung-Won; Na, Hyo-Seok
Abstract : Intubation with videolaryngoscopy has become popular in various clinical settings. However, despite the use of a videolaryngoscope, difficult intubation still exists and intubation failure has been reported. This retrospective study assessed the efficacy of the 2 maneuvers in improving the glottic view during videolaryngoscopic intubation. The medical records of patients who underwent videolaryngoscopic intubation and whose glottal images were stored in electronic medical charts were reviewed. The videolaryngoscopic images were divided into 3 categories according to the applied optimization techniques as follows: conventional method, with the blade tip located in the vallecular; backward-upward-rightward pressure (BURP) maneuver; and epiglottis lifting maneuver. Four independent anesthesiologists scored the visualization of the vocal folds using the percentage of glottic opening (POGO, 0–100%) scoring system. A total of 128 patients with 3 laryngeal images were analyzed. The glottic view was the most improved in the epiglottis lifting maneuver among all the techniques. The median POGO scores were 11.3, 36.9, and 63.1 in the conventional method, BURP, and epiglottis lifting maneuver, respectively ( P < .001). There were significant differences in the distribution of POGO grades according to the application of BURP and epiglottis lifting maneuvers. In the POGO grades 3 and 4 subgroups, the epiglottis lifting maneuver was more effective than the BURP maneuver in improving the POGO score Inadequate visualization of the vocal folds occurred even when intubation was performed using a videolaryngoscope. The application of optimization maneuvers, such as BURP and epiglottis lifting by the blade tip, could improve the glottic view.